Efficiency Analysis of Macedonian and Croatian Banking Sectors with DEA - Violeta Cvetkoska; Katerina Fotova Čiković (Economy, Business and Development: An International Journal (EB&D), 2021)
The aim of this paper is to measure and analyze the relative efficiency of commercial banks in two developing countries, the Republic of North Macedonia and the Republic of Croatia by using the leading non-parametric methodology for measuring performance, data envelopment analysis (DEA). We follow Banker et al. (2010) in the selection of variables and the model. We have applied the output-oriented BCC DEA model on a sample of 14 Macedonian and 20 Croatian commercial banks in the period from 2015 to 2019. Outliers are identified and excluded by using the Banker and Gifford (1988) super efficiency procedure, and the BCC output-oriented model is rerun with a sample of 11 Macedonian and 19 Croatian bank. We provide relative efficiency scores for each bank in both sectors, as well as an average score for the banking sectors. In addition, we analyze few banks for both sectors that have decreased or increased the efficiency, or show variable results over time. Besides, we explain how inefficient banks can improve the efficiency in future by setting targets for improvement. Our study provides valuable information for banking management and regulatory bodies.
Keywords: C67; G21; 330; banking sector; BCC; DEA; developing countries; relative efficiency